LEXICAL TRANSFORMATIONS AND ITS TYPES - Khudoyberganova Durdona ismail qizi (Лучшие интеллектуальные исследования, 2023)
Abstract: Here is a description of lexical change and its types. Excerpts from the novel are also given. As it is clear, lexical transformation is related to the translation of word. Such kinds of scientific facts and examples are also can be seen.